Influence of Buddha in the literature of Om Prakash Valmiki: ओम प्रकाश बाल्मीकि के साहित्य में बुद्ध का प्रभाव - Prasad, Jagannath (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Om Prakash Valmiki, a prominent figure in Dalit literature, has shown the profound influence of Buddha's thoughts and teachings in his literature. The principles of social justice, equality and non-violence clearly emerge in his writings, which are the key elements of Buddha's teachings. Valmiki has presented Buddha's thoughts as a guide for the suffering, struggle and liberation of Dalit society. This influence in his literature can be seen as an attempt to awaken Dalit consciousness and inspire social change. Abstract in Hindi Language: ओम प्रकाश बाल्मीकि, दलित साहित्य के प्रमुख लेखक, ने अपने साहित्य में बुद्ध के विचारों और शिक्षाओं का गहरा प्रभाव दिखाया है। उनके लेखन में सामाजिक न्याय, समानता और अहिंसा के सिद्धांत स्पष्ट रूप से उभरते हैं, जो बुद्ध की शिक्षाओं के प्रमुख तत्व हैं। बाल्मीकि ने दलित समाज की पीड़ा, संघर्ष और मुक्ति के लिए बुद्ध के विचारों को एक मार्गदर्शक के रूप में प्रस्तुत किया है। उनके साहित्य में यह प्रभाव दलित चेतना को जागृत करने और सामाजिक बदलाव के लिए प्रेरित करने के प्रयास के रूप में देखा जा सकता है। Keywords: बुद्ध के विचार, दलित चेतना, साहित्य